Paid summer undergraduate internships are one strategy to increase diversity in genetic counseling. - Kessler, Lisa Jay; Conway, Laura J.; Love, Rosaria; Valverde, Kathleen D. (Journal of Genetic Counseling, 2023)
The genetic counseling profession has attempted to enhance the diversity of its workforce since its inception but does not yet reflect the demographics of the United States. One barrier to entry into genetic counseling programs may be the ability to gain exposure to the profession prior to applying for entry. Many applicants participate in unpaid shadowing experiences, which could be a limitation to students from underrepresented backgrounds who may be less familiar with the field or who cannot forgo a salary. To address this concern, the University of Pennsylvania Master of Science in Genetic Counseling Program developed a six‐week, paid summer internship designed for undergraduates interested in genetic counseling and from underrepresented backgrounds in the field. Students were recruited via social media and word of mouth. Three undergraduates participated in the first year and four in the second year. Participants received lectures on basic topics in genetics and medical genetics, engaged in workshops and panel discussions, attended rounds and case conferences, interacted with genetic counseling mentors, and were able to shadow genetic counselors in the clinic. Benefits to the interns included enhanced appreciation for the field, development of connections with practicing genetic counselors, and development of connections with each other. The program received positive and constructive feedback and has been continued for future summers.